DESIGN AND EVALUATION OF LOW-CARBON CONSTRUCTION MATERIALS MADE WITH WASTE - Lei, Zehao (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2024)
Energy, food and water sustain modern human life. Oil refineries, power plants, food factories, and water purification plants run non-stop throughout the year providing the essential goods and commodities upon which modern society relies. These facilities, operating around the clock, generate various wastes while offering convenience to humans. These wastes are often disposed of in passive stockpiles or landfills, occupying extensive land and posing threats to the environment. Portland cement (PC)-based concrete ranks as the world's second most utilized commodity, surpassed only by water, and forms the backbone of most of the infrastructure and housing. However, in the eco-conscious 21st century, cement and concrete are continuously blamed for their contribution to carbon emissions and overexploitation of resources. The construction industry must embrace green development practices to fulfil the imperative of carbon neutrality. This research designs and evaluates geopolymers made with waste. It also measures the reactivity of wastes that can be used as PC clinker replacements to produce low-carbon cements. Geopolymer is an exemplary model of circular economy as it is primarily derived from industrial waste and transforms waste into a cementing material with a considerably lower carbon footprint than Portland cement. In this study, four types of solid waste--spent fluid catalytic cracking catalyst (FCC), alum sludge (AS) crops biomass ash (CBA) and olive pit ash (OBA) --collected from oil refineries, drinking water purification plants, biomass power plants and olive oil producers were utilized to produce geopolymers. Their properties, including chemical and mineral composition, particle size distribution, specific surface area, morphology, and reactivity were investigated. The mechanical performance, microstructure and durability of geopolymers resulting from these wastes were studied after component optimisation. Additionally, a life cycle assessment was conducted on selected geopolymers to compare their environmental impact to that of Portland cement. All wastes are reactive and can be used to produce low-carbon cement either as supplementary cementitious materials (SCMs) or in geopolymer technology. FCC is semi-crystalline and mainly composed of faujasite, a reactive zeolite. SiO2 and Al2O3 account for over 90% of the FCC's chemical composition. Chemical and mechanical methods confirmed its high reactivity. AS is an amorphous waste consisting mainly of organic matter and Al2O3, hence it is potentially active. However, it requires treatment as its high organic content may hinder pozzolanic and geopolymerisation reactions. CBA is highly crystalline as it is produced under controlled, high-temperature calcination. Although it mainly consists of SiO2 and Al2O3, the crystalline structure of its main components (quartz and albite) limits reactivity. The OBA is a unique waste consisting mainly of K2O and CaO. The low SiO2 and Al2O3 suggest low reactivity. However, its high alkali content allowed us to use it as a novel, low-carbon activator to produce low-carbon cement. Following the results of waste characterization, some wastes were treated to enhance their reactivity. High-temperature calcination, oxidation and acid etching did not significantly improve the reactivity of FCC. However, alkali fusion with 15% NaOH converted FCC into an amorphous substance, enhancing its reactivity but significantly increasing its carbon footprint. AS, was pyroprocessed at 800 C to remove organic matter and moderate its reactivity, preventing flash setting due to the high content of reactive aluminium. High-crystallinity CBA, treated with alkali fusion and 25% NaOH, showed increased reactivity due to the decomposition of quartz and albite into soluble silicates. Building on this foundation, the wastes were used as precursors and blended with ground granulated blast-furnace slag (GGBS) and fly ash (FA) to develop two-part and one-part geopolymers. In two-part systems, FCC and CBA were mixed with GGBS or FA and activated with sodium silicate solutions to produce geopolymers. FCC-based geopolymers exhibited excellent compressive strengths of 45-57 MPa. Alkali-fused CBA-based geopolymers showed improved mechanical properties compared to raw CBA-based geopolymers from 29.83 MPa to 46.47 MPa. Furthermore, high calcium systems including GGBS demonstrated superior performance, including robustness and shorter setting times. The mechanical properties of FA-mixed geopolymers were found to be highly sensitive to mixing ratios and activator composition which emphasized the importance of optimizing the design. One-part geopolymer systems were studied using AS, CBA and OBA blended with GGBS. Optimal AS geopolymer mix ratios (SiO2/Al2O3=2.5, Na2O/Al2O3=1.0) achieved a compressive strength of 66.50 MPa. Additionally, a reliable binder can be produced with 30% raw CBA and 70% GGBS, activated by sodium carbonate and sodium silicate featuring a compressive strength of 46.09 MPa and a quick setting pattern. Alkali-fusing CBA allowed to increase in CBA content to 50%; the resulting geopolymer achieved a compressive strength of 45 MPa. OBA, due to its high alkali content, was effectively used as an activator, reaching 15.43 MPa alone and 43.94 MPa when optimized with sodium carbonate. All the geopolymers showed a dense and compact matrix. The durability of the geopolymers was estimated by measuring their resistance to wet-dry cycles, sulphate attack and high-temperature resistance. Geopolymers prepared with high activator dosage and alkali-fused precursors showed poor performance in cycling tests. This evidenced that Na+ content significantly undermines durability. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) analyses revealed that repeated salt dissolution and crystallization were key factors in mechanical loss rather than matrix composition changes. Moreover, high temperatures significantly reduced strength due to thermal expansion disparities. The amorphous and dense microstructure was maintained when calcined below 450-600 C. Finally, the environmental impacts of geopolymers were evaluated through a life cycle assessment (LCA). The results indicate that the production method of activators and carbon allocation in GGBS significantly influence the environmental impact. Environmentally friendly activator production methods can substantially reduce carbon emissions. When GGBS carbon allocation is based on its economic value, as a by-product rather than waste, geopolymer shows 38-78% lower carbon emissions compared to CEM I and CEM II, except for the AS geopolymer. The higher carbon emissions of the AS geopolymer are due to the high carbon content of the AS waste. This comprehensive analysis underscores the potential of optimized geopolymers as sustainable construction materials.
APPROVED
Keywords: Industrial waste; Agricultural waste; Reactivity; Low-carbon cement; Alkali fusion; Geopolymer; Durability; Environmental impact; Life cycle assessment